Pressure Injury Prevention and Wound Management for the Patient Who Is Actively Dying: Evidence-Based Recommendations to Guide Care. Issue 6 (November 2020) - Vickery, Jessica; Compton, Lauren; Allard, Jackie; Beeson, Terrie; Howard, Joycelyn; Pittman, Joyce
Abstract : Preventing pressure injuries and wound deterioration can be challenging for the patient at the end of life. Pressure injuries are often deemed unavoidable when a patient is actively dying; however, the time frame for this process is variable. As the skin fails in an actively dying patient, interventions should align with the patient and family's goals. This integrative literature review defines essential concepts to pressure injury and wound management during this final stage of life including (1) actively dying, (2) end of life, (3) palliative care, and (4) comfort measures. We also provide clinically relevant, evidence-based recommendations for pressure injury prevention and wound management of the patient who is actively dying.